Intercellular communication is crucial in the regulation of healthy aging via exosomes - Sun, Huifang; Xia, Tengyuan; Ma, Shuting; Lv, Tao; Li, Yuhong (Pharmacological research, 2025)
The hallmarks of aging encompass a variety of molecular categories (genomic, telomeric, and epigenetic), organelles (proteostasis, autophagy, and mitochondria), cellular components (including stem cells), systems (such as intercellular communication and chronic inflammation), and environmental factors (dysbiosis and nutrient sensing). These hallmarks play a crucial role in the aging process. Despite their intricate interconnections, the relationships among the hallmarks of aging remain unclear. Although the boundaries between these hallmarks may be indistinct, they exhibit interdependence, with the influence of one hallmark extending to others. Building on this foundation, we investigated the interrelations among the various hallmarks of aging and provided a systematic overview of their logical relationships, proposing that cellular communication plays a crucial role in the aging process. Exosomes function as a primary mode of cellular communication and significantly impact the aging process. Therefore, we propose utilizing exosomes as valuable tools for understanding the mechanisms of aging and addressing age-related concerns. Exosomes may represent a novel approach for the treatment and diagnosis of aging-related conditions in animals. Furthermore, our research reveals that exocytosis in young nematodes slows the aging process, while exocytosis in aged nematodes has the opposite effect, accelerating aging. In conclusion, exosomes act as intercellular messengers that influence the maintenance of a healthy aging process and link the hallmarks of aging with indicators of well-being. [Display omitted] •Intercellular communication is essential for elderly people's health.•Exosomes regulate communication among senescent cells: the bystander effect.•Exosomes as biomarkers of aging.•Intercellular communication(exosomes) contributes to regulating the process of healthy aging.